New approaches to monetary economics proceedings of the Second International Symposium in Economic Theory and Econometrics - Barnett, William A.; Singleton, Kenneth J. 1951- (International symposia in economic theory and econometrics, 1987)
New Approaches to Monetary Economics brings together presentations of innovative research in the field of monetary economics. Much of this research develops and applies approaches to modelling financial intermediation, aggregate fluctuations, monetary aggregation and transactions-motivated monetary equilibrium. The contents of this volume comprise the proceedings of the second in a conference series entitled International Symposia in Economic Theory and Econometrics. This conference was held in 1985 at the IC2 Institute at the University of Texas at Austin. The symposia in this series are sponsored by the IC2 Institute and the RGK Foundation. New Approaches to Monetary Economics, edited by Professors William A. Barnett and Kenneth J. Singleton, consists of five parts. Part I examines transactions-motivated monetary holding in general equilibrium; Part II, financial intermediation; Part III, monetary aggregation theory, Part IV, issues in aggregate fluctuation; and Part V, theoretical issues in the foundations of monetary economics and macroeconomics